Combining mathematics and music in teaching - Korhonen, Anssi (LUMAT-B: International Journal on Math, Science and Technology Education, 2022)
Mathematics and music have plenty in common. In music you can find fractions, their operations, divisibility, sequences and even logarithms and exponents. In this case, it is also possible to combine mathematics and music in teaching and give a new perspective and concreteness alongside the traditional lessons. The article deals with the similarities between mathematics and music, that are presented on the course LUMATIKKA3: Mathematics and Art, but broaden the viewpoint to brain activity and, more widely, the different methods of combining mathematics and music in basic education and upper secondary teaching.